Structural effects of meso-halogenation on porphyrins - Senge, Mathias (My University, 2021)
The use of halogens in the crystal engineering of supramolecular porphyrin assemblies has been a topic of strong interest over the past decades. With this in mind we have characterized a series of direct meso-halogenated porphyrins using single crystal X-ray crystallography. This is accompanied by a detailed conformational analysis of all deposited meso-halogenated porphyrins in the CSD. In this study we have used the Hirshfeld fingerprint plots together with normal-coordinate structural decomposition and determined crystal structures to elucidate the conformation, present intermolecular interactions, and compare respective contacts within the crystalline architectures. Additionally, we have used density functional theory calculations to determine the structure of several halogenated porphyrins. This contrasts conformational analysis with existing X-ray structures and gives a method to characterize samples that are difficult to crystallize. By using the methods outlined above we were able to deduce the impact a meso halogen has on a porphyrin, for example, meso-halogenation is dependent on the type of alternate substituents present when forming supramolecular assemblies. Furthermore, we have designed a method to predict the conformation of halogenated porphyrins, without need of crystallization, using DFT calculations with a high degree of accuracy.
Keywords: Conformational analysis; Crystal engineering; Halogenation; Macrocycles; Porphyrins